2014
DOI: 10.7314/apjcp.2014.15.9.4029
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome is Associated with More Aggressive Prostate Cancer

Abstract: Purpose: The aim of this study was to analyze any association between the metabolic syndrome (MetS) and risk of prostate cancer (PCa) and cancer grade among men undergoing radical prostatectomy for PCa. Materials and Methods: 50 patients with MetS and 50 patients without MetS who undervent radical prostatectomy (RP) were included in the study. Age at biopsy, height, weight, digital rectal examination (DRE), pre-biopsy PSA levels, prostate volume, histopathologic diagnosis after surgery and gleason scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…PSA levels influenced by many factors like age, race, the Metabolic Syndrome or even Body Mass Index (BMI) and alcohol consumption (Chiu et al, 2011;Bashir et al, 2014;Daniyal et al, 2014;Ozbek et al, 2014;Woo et al, 2014). But the most important disadvantage of the PSA test is its low specificity which means that a high percentage of the men are negative on initial biopsy (Jansen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PSA levels influenced by many factors like age, race, the Metabolic Syndrome or even Body Mass Index (BMI) and alcohol consumption (Chiu et al, 2011;Bashir et al, 2014;Daniyal et al, 2014;Ozbek et al, 2014;Woo et al, 2014). But the most important disadvantage of the PSA test is its low specificity which means that a high percentage of the men are negative on initial biopsy (Jansen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A deeper research into the factors that differ significantly across these continents may answer the questions regarding its incidence and causative factors. The foremost risk factors that may underlie these regional/ethnic differences could be endocrine variations, genetic polymorphisms (ZeiglerJohnson et al, 2002) altered hormonal status (Garfinkel, 1986), socioeconomic status (Nomura and Kolonel, 1991) and obesity and diet (Stephen and Brady, 2005;Girling et al, 2007) Diet, disturbed glucose metabolism, and metabolic syndrome are extremely interesting factors for in depth exploration in relation to the risk of prostate cancer (Long et al, 2012;McGrowder et al, 2012;Tewari et al, 2012;Ozbek et al, 2014, Pandeya et al 2014 In an earlier study, we presented that body mass index and waist to hip ratio were significantly higher in prostate cancer in 1 , Singh Rajender 2 *…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies have shown a close link between obesity, serum lipids and prostate cancer [3,4]. Elevated triglycerides (TGs) and low highdensity lipoprotein (HDL) levels were significantly associated with high-grade prostate cancer, albeit this relationship was not consistent between reports [5][6][7][8]. Moreover, low HDL was associated with adverse pathological findings after radical prostatectomy (RP) [9].…”
Section: Introductionmentioning
confidence: 99%